2020
DOI: 10.3892/ol.2020.11418
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA BRM promotes proliferation and invasion of papillary thyroid carcinoma by regulating the microRNA‑331‑3p/SLC25A1 axis

Abstract: Long non-coding RNA BRM (lncBRM) was first identified in liver cancer stem cells and was reported to promote multiple cancer types. However, the function of lncBRM in papillary thyroid carcinoma (PTC) remains unclear. The primary focus of the present study was to determine the biological role of lncBRM in PTC. Reverse transcription-quantitative PCR assays revealed that lncBRM was upregulated in PTC tissues and cells. Cell Counting Kit-8, Transwell invasion and colony-formation assays were performed to assess c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…The fundamental role of CIC and its upregulation in cancer, inflammation, and beyond is well described in a recent review article by Mosaoa et al [ 187 ]. CIC was found to be overexpressed in different types of cancer: breast cancer [ 188 ], colorectal cancer [ 189 ], prostate cancer [ 190 ], hepatomas [ 191 ], thyroid carcinoma [ 192 ], and others. These multiple studies clearly demonstrate that CIC is essential for the proliferation of different types of cancer cells.…”
Section: Definition Of the “ β -Oxidation Shuttle”mentioning
confidence: 99%
“…The fundamental role of CIC and its upregulation in cancer, inflammation, and beyond is well described in a recent review article by Mosaoa et al [ 187 ]. CIC was found to be overexpressed in different types of cancer: breast cancer [ 188 ], colorectal cancer [ 189 ], prostate cancer [ 190 ], hepatomas [ 191 ], thyroid carcinoma [ 192 ], and others. These multiple studies clearly demonstrate that CIC is essential for the proliferation of different types of cancer cells.…”
Section: Definition Of the “ β -Oxidation Shuttle”mentioning
confidence: 99%
“…From the same families of genes discovered to be the target of several microRNAs we mention CXCL-12/16 [16,86], CCNG-1/2 [17,100], IRS-1/2 [19,107], FGF-2/FR [28,112], CCDC-6/67 [52,128], FOX-O1/E1/M1 [27,55,76], ITGA-3/6 [55,61], SL-1A5/25A1 [56,118], MAP-2K4/K1/4K3 [71,78,120], and SOX 11/12/2 [84,95,117].…”
Section: One Gene Can Be Targeted By Several Micrornasmentioning
confidence: 99%
“…Recent studies have shown that in patients affected by papillary thyroid carcinoma (PTC), the long non-coding non-coding RNA for association with Brahma, (lncBRM), is significantly upregulated, correlating with poor overall survival [ 47 ]. lncBRM targets CIC activity via the microRNA miR-331-3p and promotes PTC cell proliferation, migration and invasion, an effect that is rescued by inhibiting CIC.…”
Section: Cic Inhibition Inhibits the Growth Of Different Tumor Typmentioning
confidence: 99%